2021
DOI: 10.1002/ange.202115225
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Anionic Inorganic Module—An Efficient Approach Towards Highly Efficient Blue‐Emitting Copper Halide Ionic Hybrid Structures

Abstract: Copper halide based organic-inorganic hybrid semiconductors exhibit great potential as light-emitting materials with excellent structural variety and optical tunability. Among them, copper halide hybrid molecular compounds with discrete inorganic modules are particularly interesting due to their high quantum efficiency. However, synthesizing highly efficient blue-emitting molecular clusters remains challenging. Here, we report a novel and facile strategy for the design and synthesis of highly luminescent coppe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 61 publications
(11 reference statements)
0
14
0
Order By: Relevance
“…[39,40] A single band feature was observed for all compounds, with an average full-width at half-maximum (FWHM) of ~100 nm, which has been observed for many CuX-based hybrid materials. [41,42] The internal quantum yields (IQYs) of all three compounds were determined at room temperature under 360 nm excitation, and are listed in Table 2. The optical bandgaps of the compounds range from 2.3 to 2.6 eV, estimated from their absorption edges as shown in Fig.…”
Section: -mentioning
confidence: 99%
See 1 more Smart Citation
“…[39,40] A single band feature was observed for all compounds, with an average full-width at half-maximum (FWHM) of ~100 nm, which has been observed for many CuX-based hybrid materials. [41,42] The internal quantum yields (IQYs) of all three compounds were determined at room temperature under 360 nm excitation, and are listed in Table 2. The optical bandgaps of the compounds range from 2.3 to 2.6 eV, estimated from their absorption edges as shown in Fig.…”
Section: -mentioning
confidence: 99%
“…The ΔE (S 1 -T 1 ) of compound 1 was estimated to be 0.056 eV, similar to that of other reported compounds exhibiting efficient TADF process. [42,49,51] Such small energy splitting is essential to boost the efficient TADF at ambient temperatures. In addition, only very small blue shift of the emission spectra of compound 1 was observed by increasing temperature from 77 K to 298 K, which can be attributed to the indistinguishishable energy of S 1 and T 1 .…”
Section: -mentioning
confidence: 99%
“…Recently, Liu and Ouyang reported that a family of strongly blue-emitting copper halide hybrid ionic structures was prepared. All these materials contain Cu 2 L 5 or CuL 4 polyhedrons in their single crystal structures …”
Section: Introductionmentioning
confidence: 99%
“…All these materials contain Cu 2 L 5 or CuL 4 polyhedrons in their single crystal structures. 42 It is widely known that the emission property of metal halides is determined by the coordination environment of the core metal. 43,44 Further, according to these novel copper(I)based luminescent materials, it seems to be that the optical properties are related to the coordination number of Cu I .…”
Section: ■ Introductionmentioning
confidence: 99%
“…These results clearly suggest the typical CC emission nature of compounds 1 and 2, similar to previously reported AIO structures made of N-monoalkylated TEDs. 6,19,24 Interestingly, the influence of involving aromatic systems in the Cu−N coordination has been successfully captured by the calculations. The results of compounds 3−5, in which aromatic N atoms are coordinated directly to their inorganic motifs, demonstrate different characteristics compared to the cases in compounds 1 and 2.…”
Section: ■ Results and Discussionmentioning
confidence: 96%